Taman Negara Malaysia's National Park - Teoh, Patrick; Perbadanan Kemajuan Pelancongan Malaysia ([s.n.] : Camelite Film Sdn. Bhd., 1995)
This video focuses visitors on the natural beauty and spots in the park.
Copy available in DVD format.
Narrator, Patrick Teoh.
Keywords: National parks and reserves -- Pahang; National parks and reserves -- Malaysia; Documentaries and factual films and video